Available energy analysis of solar-assisted heat pump - Özmen, Akif. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
The aim of this study is to perform the second law analysis for solarassisted heat pump system. For this purpose, the computer simulation of solarassisted heat pump system is performed and the results are obtained for typical days of each month of December, January, February and March. Also, the same task is performed for solar collector system and heat pump system. During the analysis, five different solar collector areas are used for both the solarassisted heat pump system and solar collector system, summing up to eleven different systems consisting three main systems. The conventional boiler is used as auxiliary energy source for all of the systems. The exergetic efficiency, or, second law efficiency is defined, formulated and reduced for each of the systems. The exergetic efficiencies and coefficient of performances are calculated by computer using fifteen minutes computer stePs and comparison is performed among the systems.
Keywords: Heat pumps.; Energy conservation.; Solar heating.